The required expression is 2y² - 4y + 5.
Step-by-step explanation:
We have to find the sum of first 2 expressions and then subtracting an expression, let us consider a, to give the third expression. We have to find a.
y² + 5y -1 + 3y² - 2y + 4
We have to group the like terms and doing the addition as,
= y² + 3y² + 5y -2y -1 + 4
= 4y² + 3y + 3
Now we have to subtract an expression a from the above sum to get the third expression.
4y² + 3y + 3 - a = 2y² + 7y - 2
Now we have to group the terms as,
a = 4y² + 3y + 3 - (2y² + 7y - 2)
= 4y² + 3y + 3 - 2y² - 7y + 2
Rearranging the terms as,
a = 4y² - 2y² + 3y - 7y + 3 + 2
= 2y² - 4y + 5
So the required expression is 2y² - 4y + 5.